(untitled) (Ius Novum, 2019)
Reimbursement of excise duty is an essential element of this tax recovery process. Tax authorities refuse to comply with the obligation to reimburse excise duty on an intra-Community supply (export) of excise goods within a statutory period, although the obligation is binding on them. When ensuring the tightness of the tax system, the tax authority should first compare the content of the transposed provision of Directive 2008/118/EC and the Excise Duty Act. In the event that the EU rules conflict with the wording of the national provision and the taxpayer requests that the EU rule be applied in the manner specified in the Directive, the tax authority should refuse to apply the rule of national law resulting from the Excise Duty Act, and make it possible for the taxpayer to benefit from the EU regulation. It should be borne in mind that the tax authority is under the obligation to interpret national law in compliance with the purpose of the Directive and such interpretation should be preceded by determination of that purpose. A method of interpretation must ensure that the purpose of the Directive is determined. The objective of the analysis offered herein is to explore issues pertaining to interpretation of the Directive concerning general arrangements for excise duty. Due to improper implementation, the arrangements ensured the tightness of the tax system through legal interpretation. Nevertheless, it is claimed that grounds for proper implementation of the Directive are provided by the obligation to follow a pro-EU interpretation that should be preceded with reconstruction of the purpose of the regulation as defined in the recitals, as far as possible in order to achieve the effect specified in the Directive 2008/118/EC.